ADOPSI TEKNOLOGI SISTEM PERTANIAN TERINTEGRASI BAGI PETANI DALAM USAHA MEMAKSIMALKAN KEUNTUNGAN DAN UTILITAS - Sukanteri, Ni Putu; Lestari, Putu Fajar Kartika; Suryana, I Made (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
Technological changes in agriculture and information flow of increasingly advanced and growing farming system requires agricultural actors to be better understood with the current technological sophistication. Technological advances are expected to assist farmers in staggering the results of their farming. Integrated agricultural systems are developed to increase production per hectare of land. Based on the background, it is necessary to conduct research on the adoption of integrated agricultural system technology in Tabanan. The purpose of this research is to know the response of farmers to adoption of integrated agricultural system technology in Tabanan, and factors influencing the process related to transfer adoption technology integrated agriculture system in Tabanan.The research was conducted in Selemadeg Timur of Tabanan Regency, with the consideration that there are three groups of farmers implementing integrated Agriculture System built by the Provincial Office of Agriculture of Bali-based and producing their own bio pesticide from livestock waste. research shows that the farmer's response to adoption of integrated agricultural system technology in Tabanan is very fast, this is indicated by the time required by farmers to adopt the technology within 5 years. Factors affecting the process associated with the adoption of agricultural technology transfer system integrated in Tabanan is education, frequency follow the broadcast.